2017
DOI: 10.1093/cid/cix791
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Novel Human Rabies Monoclonal Antibody to Human Rabies Immunoglobulin for Postexposure Prophylaxis: A Phase 2/3, Randomized, Single-Blind, Noninferiority, Controlled Study

Abstract: CTRI/2012/05/002709.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 20 publications
0
39
0
1
Order By: Relevance
“…patients infected with the Ebola virus highlight the superiority of mAb treatment over convalescent plasma treatment (7,8). Moreover, mAb therapy has been proven safe and effective against influenza virus, rabies virus, and respiratory syncytial virus (RSV) (9)(10)(11).…”
mentioning
confidence: 99%
“…patients infected with the Ebola virus highlight the superiority of mAb treatment over convalescent plasma treatment (7,8). Moreover, mAb therapy has been proven safe and effective against influenza virus, rabies virus, and respiratory syncytial virus (RSV) (9)(10)(11).…”
mentioning
confidence: 99%
“…Este tem a capacidade de se ligar a um epítopo da glicoproteína rábica. 41 Este estudo demonstrou que uma dose de 10 UI/kg de Rabishield TM produz imunidade equiparável a 20 UI/kg de IGR. 42 Sendo este o único anticorpo monoclonal licenciado e dadas as limitações de acesso à IGR, o seu uso está autorizado em zonas geográficas seleccionadas.…”
Section: Perspectivas Futuras A) Prevençãounclassified
“…So far, though, activities have been most advanced in respect to rabies, for which at least two different products are considered [19]. For one of these, a single human monoclonal antibody (SII-RMAb), a recently completed noninferiority controlled trial concluded it as a potential safe and potent alternative to human rabies immunoglobulin-containing postexposure prophylaxis regimen [57].…”
Section: Replacement Of Polyclonal Antibodiesmentioning
confidence: 99%